2019
DOI: 10.1021/acs.jafc.8b04996
|View full text |Cite
|
Sign up to set email alerts
|

New Alkylitaconic Acid Derivatives from Nodulisporium sp. A21 and Their Auxin Herbicidal Activities on Weed Seeds

Abstract: Five alkylitaconic acid (AA) derivatives, including two novel compounds, epideoxysporothric acid (2) and sporochartine F (5), and three known compounds, deoxysporothric acid (1), deoxyisosporothric acid (3), and 1-undecen-2,3dicarboxylic acid (4), were obtained from the fermentation culture of the endophytic fungus Nodulisporium sp. A21. The auxin herbicidal activities of compounds 1−4 against weed seeds were investigated under laboratory conditions. In general, the tested compounds displayed radicle growth pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Cao et al . (2019) verified a similar pathway for the biosynthesis of three alkylitaconic acids and one derivative; deoxysporothric, epideoxysporothric, 1‐undecen‐2,3‐dicarboxylic and deoxyisoporothric acids, using 13 C labelling experiments. Given these findings, alkylitaconic acids are generally synthesized by the condensation of acyl‐CoAs derived from fatty acids with oxaloacetic acid via similar biosynthetic pathways.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…Cao et al . (2019) verified a similar pathway for the biosynthesis of three alkylitaconic acids and one derivative; deoxysporothric, epideoxysporothric, 1‐undecen‐2,3‐dicarboxylic and deoxyisoporothric acids, using 13 C labelling experiments. Given these findings, alkylitaconic acids are generally synthesized by the condensation of acyl‐CoAs derived from fatty acids with oxaloacetic acid via similar biosynthetic pathways.…”
Section: Introductionmentioning
confidence: 68%
“…Previously, we reported that 9-HHIA and 10-HHIA produced by A. niger S17-5 have cytotoxic and polymer building block properties (Aso et al 2020;Sano et al 2020). Related studies have predicted that 9-HHIA and 10-HHIA are synthesized by the condensation of octanoyl-CoA, which is derived from caprylic acid, with oxaloacetic acid (Guti errez et al 2002;Cao et al 2019;Palys et al 2020). However, there have been no studies regarding the effects of the addition of caprylic acid on 9-HHIA and 10-HHIA production.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…During our recent studies examining bioactive metabolites from endophytes, 15–18 Alternaria alternata ZHJG5, a Cercis chinensis ‐associated fungus, showed strong antibacterial effects against many phytopathogens. A study of the crude extract of A. alternata ZHJG5 led to the discovery of five new polyketide derivatives, isotalaroflavone ( 2 ), (+/−)‐5′‐dehydroxytalaroflavone ( 3a/3b ), (+)‐talaroflavone ( 4b ) and bialternacin G ( 7 ), along with five known compounds.…”
Section: Introductionmentioning
confidence: 99%
“…As part of our explorative effort to find structurally diverse and/or bioactive natural products from endophytic fungi, we have identified sporothriolide, prochaetoviridin A, chaetoindolin A, alkylitaconic acid (AA) derivatives (epideoxysporothric acid, and sporochartine F) [10–12] . Among them, sporothriolide exhibited potent antifungal and alkylitaconic acid derivatives reported for herbicidal activities.…”
Section: Introductionmentioning
confidence: 99%